Potential Applications of Ultrasonic Parametric Array Loudspeakers (PALs) in Room Acoustic Measurements - WĘGRZYN, Filip; PILCH, Adam (Archives of Acoustics, 2025)
In this paper, the potential use of parametric array loudspeakers (PALs) in acoustic measurements of the room is analysed, especially in the assessment of the effectiveness of reflective panels and intentionally angled surfaces. PALs are sound sources capable of emitting highly directional acoustic beams within the audible frequency range. Their operation is based on the emission of a high-frequency (ultrasonic) carrier modulated so that, through nonlinear demodulation in air, audible sound is generated. This process results in a narrow, focused sound beam, enabling precise acoustic emission. To explore PALs potential for acoustic measurement applications, the propagation behaviour of PAL-generated signals is first investigated under free-field conditions, focusing on how different surface types influence sound reflection. Subsequent experiments are carried out in a controlled indoor space, where impulse responses are recorded for various beam incidence angles and receiver positions. The collected data are used to generate sound-level distribution maps, allowing for the visualization and quantification of reflected sound coverage areas. The results show that PALs produce beams with substantially reduced lateral dispersion compared to conventional loudspeakers, enabling precise identification of reflection points and incidence angles. This directional precision makes it possible to accurately assess how effectively the reflective acoustic elements and structures shape the sound field within the room. Overall, these findings may contribute to optimising sound design in acoustically complex environments.